The potential for controlling postflowering pests of cowpea, Vigna unguiculata Walp., using neem, Azadirachta indica A. Juss - Jackai, L.E.N.; Inang, E.E.; Nwobi, P. (Informa UK Limited, 1992)
The insecticidal activity of neem, Azadirachta indica A. Juss., was tested on two major cowpea pests using different concentrations of aqueous extracts, and powders of both neem seed and kernel. The pests were larvae of Maruca testulalis Geyer (Lepidoptera: Pyralidae), the legume pod borer and Clavigralla tomentosicollis Stäl (Hemiptera: Coreidae), the cowpea coreid bug. Ife Brown, an improved local cowpea variety, and IT84S‐2246, a breeding line from IITA grain legume programme, were used in the study. Neem proved effective in acting as an insecticide and affected the rates of development of both pests at concentration as low as ca. 9% solution (wt/vol.). Imaginal survival was found to decrease with increasing neem concentration, but a point was reached where further increase in the amount of neem produced no significant changes in survival rates. Most bug nymphs died within 9 days of infestation but those which survived to adult in the 5% solution (wt/vol.) of the seed extract took almost twice the normal developmental time, and the emerging adults appeared weakened. While both the neem extracts and powder proved effective in suppressing development the former were more effective. This is the first report on the potential use of neem in the protection of cowpeas against C. tomentosicollis and M. testulalis.